Professional development programmes for teachers and educational managers of the education sector in Tanzania: towards a holistic approach - Lyamtane, Eugene; Mosha, Herme Joseph (Papers in Education and Development, 2024)
This article examines in-service training (INSET) and teachers’ professional development (TPD) as critical tools for improving educational quality in Tanzania through a holistic approach. Unlike stand-alone or singular approaches, a holistic perspective recognises the interconnected elements necessary to enhance teaching practices and achieve high-quality education. While primarily focusing on teachers, the study also highlights the importance of addressing the needs of strategic educators who contribute significantly to improved learning outcomes. These programmes aim to address training gaps, respond to evolving educational demands, and adapt to societal complexities. The methodology involved document analysis, key research findings, consultancy experiences, and professional expertise. The study underscores the importance of balanced PD programmes that enhance subject knowledge, integrate modern pedagogical skills, leverage technology, promote inclusive education, foster collaboration and professional learning communities, and adhere to ethical and professional standards. To be effective, PD programmes must be client-driven, well-planned, adequately financed, and effectively implemented. The study emphasises the need for a holistic model that addresses all critical aspects of professional development. Adopting such a model is recommended to support the country’s vision of achieving excellence, relevance, and quality in education across all levels.